Sutureless vaginal hysterectomy - Mahmoud S Mahmoud (Wolters Kluwer Medknow Publications, 2020)
Introduction The ERBE BiClamp appears to be a secure and efficient technique of vaginal hysterectomy (VH). In this study, it provided proficient operative times, and minimum loss of blood and morbidity during the procedure with satisfactory outcomes. Its utilization plays a part in the enhancement of minimally invasive gynecology and it should be promoted. Objective The aim was to evaluate the applicability of VH without suture ligation. Materials and methods A retrospective cohort study was carried out during the period between September 2017 and May 2019 in the Obstetrics and Gynecology Department, Al-Azhar University Hospital, New Damietta. A total of 62 patients posted for VH for benign conditions were enrolled after informed consent. The patients were divided into two groups: the first included 32 cases for the BVS (BiClamp) and the second control group included 30 cases with conventional suture ligation. Results The use of an electrosurgical bipolar vessel sealer resulted in shorter operative time. The median procedure time in the electrosurgical bipolar vessel sealer group was 27.75 vs 43.5 min for the suture group (P=0.005). The median value of estimated blood loss was also statistically less with electrosurgical bipolar vessel sealer [85.8 ml vs 105.4 ml for the suture arm (P=0.043)]. The incidence of complications did not differ statistically between the two groups (P>0.05). Conclusion Bipolar vessel sealer has shown a major decrease in intraoperative blood loss, procedure time, and hospital length of stay. Although complications and postoperative pain did not differ between the two groups, the sealer cases reported less visual analog scale scores compared with the other group.